An analysis of human’s needs from Islamic perspectives in Cucu Tuk Wali by Abu Hassan Morad - Abdul Aziz @ Mohd Salleh, Nur Azimah; Mohd Hanafiah, Halis Azhan; Abu Bakar, Roslina (Human Resource Management Academic Research Society, 2021)
This paper aims to analyze human’s needs from Islamic perspectives, as illustrated in a young adult novel, Cucu Tuk Wali by Abu Hassan Morad. It is a general belief that any prose fiction would utilize conflicts to generate stories. This, however, can only be materialized if such conflicts manage to highlight the actual needs of the protagonist. Therefore, the study would evolve around Liza, a young adult who is good in academics and personality, yet an unfortune one too as she has to deal with a number of conflicts in her life. Becoming a college dropout, the people of her hometown start to look down at her, none belief in her capability. At home, she feels unease as her father has just remarried her once school classmate. Liza needs to overcome these obstacles first before rectifying everything, and achieves several goals that were once seemed achieveable. In line with this, the study would scrutinize the Islamic theory of human’s needs, as proposed by Fakhr al-Din al-Razi (or widely known as al-Razi). The theory encompasses five components of human needs, namely al-U'budiyyah (the needs for devotions), Talab al-Isti'anah (the needs for supports), Talab of Istaqamah (the needs of right paths), Talab of Hidayah (the needs for guidances) and Talab of Ni'mah (the needs for rewards). These needs are said to be circulating in a man through out his life and he would always try to achieve them simultaneously. This study later finds out that in her effort to overcoming these conflicts and achieving her needs, Liza as the protagonist of the novel portrays good and favourable characterictics of a caliph and a servant of God. Due to these, she is said to possess all the five forms of needs of outlined by al-Razi in his Islamic theory of human’s needs.